Active brazing material, preparation method and application thereof

By using titanium alloy or active brazing material composed of pure titanium layer and titanium hydride layer, the problems of complex process, high cost and poor welding uniformity in the prior art are solved, and efficient and uniform brazing effect and good joint mechanical properties are achieved.

CN119525812BActive Publication Date: 2025-04-25宁波众远新材料科技有限公司 +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510103510.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-25
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

The existing active brazing materials have complex preparation processes, high cost, and poor welding uniformity, which affects the brazing efficiency and the mechanical properties of the joints.

Method used

The active brazing material composed of a titanium alloy layer or a pure titanium layer and a titanium hydride layer is used to remove the oxide film through an acid solution and hydrogenation treatment to form a titanium hydride layer, simplifying the process and reducing costs.

Benefits of technology

The uniformity and high efficiency of brazing materials are achieved, the service life is extended, and the mechanical properties and interface wetting effect of the welding area are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119525812B_ABST
    Figure CN119525812B_ABST
Patent Text Reader

Abstract

The invention discloses an active brazing material, a preparation method and an application, and belongs to the technical field of brazing materials. The active brazing material of the invention is composed of a titanium alloy layer or a pure titanium layer and a titanium hydride layer distributed on both sides thereof, the thickness of the titanium alloy layer or the pure titanium layer is 5-50 μm; the single layer thickness of the titanium hydride layer is 0.05-3 μm, and the preparation method thereof comprises the steps of acidification treatment and hydrogenation treatment of the pure titanium foil or the titanium alloy foil. The material is a large-area thin-layer welding sheet, which has the advantages of good welding uniformity and high brazing efficiency. The surface titanium hydride also makes it have a longer service life and better interface wetting effect, excellent brazing performance, good reliability, and can be used in vacuum brazing of copper alloys and ceramics, copper alloys and non-ferrous metals, and copper alloys and carbon materials, and has practical industrial application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of brazing materials, and in particular relates to an active brazing material, a preparation method and an application thereof. Background Art

[0002] Ceramic copper clad laminate is a composite material that combines a ceramic substrate with a copper metal layer. It combines the excellent conductivity of oxygen-free copper with the high insulation performance, low expansion coefficient and high mechanical strength of ceramics. It is widely used in power electronics, IGBTs and power electrical appliances. Due to the large difference in physical and chemical properties between ceramics and metals, it is difficult for metal solder to wet on the ceramic surface and the large residual stress will affect the mechanical properties of the joint.

[0003] The main processes for preparing ceramic copper-clad laminates include active metal brazing, direct copper coating on ceramic substrates, and thick film method. Compared with direct copper coating and thick film method, ceramic copper-clad laminates prepared by active metal brazing have higher bonding strength and good high temperature resistance. At present, most active brazing materials use Ag-based and Cu-based brazing fillers, among which Ti is often added to the above brazing fillers as an active metal element to increase the wettability of the active metal brazing filler on the ceramic surface and achieve a good combination of ceramic and metal.

[0004] Chinese patent CN115151371A discloses a brazing material and a method for making the same, as well as a method for making a metal-ceramic bonding substrate. The method uses an Ag solder paste mainly composed of silver powder and a small amount of titanium powder and copper powder. The welding process using the material has high requirements. More importantly, the uneven distribution of the solder paste ingredients will increase the risk of reduced reliability in the welding area. Chinese patent CN116038179A discloses a silver-copper-titanium brazing material and a preparation method and application thereof. The patent mixes silver-coated titanium hydride powder, copper powder and other metal powders to obtain a mixed powder, which is pressurized and sintered to make welding materials of different shapes. Although the material improves the brazing performance, the preparation of the material is cumbersome, time-consuming and costly.

[0005] Based on this, a brazing material with low cost, simple preparation process, convenient brazing process, good operability, high brazing efficiency, excellent performance and good reliability has been developed, which has very high industrial application value. Summary of the invention

[0006] In order to solve the above technical problems existing in the prior art, the present invention provides an active brazing material, a preparation method and an application. The brazing material of the present invention has a simple production process, low cost and high production efficiency, and the material is a large-area thin-layer welding sheet, which has the advantages of good welding uniformity and high brazing efficiency; the titanium hydride on its structural surface also makes it have a longer service life and better interface wetting effect.

[0007] Firstly, the present invention provides an active brazing material, which is composed of a titanium alloy layer or a pure titanium layer and titanium hydride layers distributed on both sides thereof.

[0008] Titanium has the advantages of good wettability, high temperature strength, stable structure and performance, and corrosion resistance as a solder. When it is in a high temperature environment of brazing, its properties are more active and it is very easy to oxidize with the surrounding contact materials to produce titanium oxide. In subsequent processing and use, these high-hardness and high-brittle titanium oxides will cause surface cracks and extend into the welded matrix, causing serious negative effects on the quality of the welded materials. The present invention modifies a titanium hydride layer of a certain thickness on the surface of the titanium alloy layer or the pure titanium layer. The active hydrogen released at high temperature has a strong reducing effect, has a good protective effect on the titanium alloy to avoid the formation of harmful phases, and can also promote the formation of good interface contact and wetting between the molten solder and the welded material, thereby improving the mechanical properties of the welding area.

[0009] Further, the thickness of the titanium alloy layer or the pure titanium layer is 5-50 μm, such as 5 μm, 6 μm, 7 μm, 10 μm, 15 μm, 20 μm, 22 μm, 25 μm, 28 μm, 30 μm, 32 μm, 35 μm, 38 μm, 40 μm, 43 μm, 45 μm, 47 μm, 50 μm, etc.; preferably 5-25 μm, more preferably 7-15 μm. When the titanium alloy layer or the pure titanium layer is too thin, it is impossible to form sufficient fusion in the welding area, and it is also necessary to use a more sophisticated welding process, but when it is too thick, it may not be easy to melt completely, resulting in a cold welding defect in the joint, all of which will reduce the mechanical properties of the joint. Only with the appropriate thickness can a good fusion zone be formed, and the bonding between titanium and copper alloy or ceramic is more firm, thereby improving the mechanical strength of the joint.

[0010] Furthermore, the content of Ti in the titanium alloy layer is ≥95wt%. Titanium foil with high titanium content can better form metallurgical bonding with the parent material during welding, and can also form a more uniform microstructure, thereby improving the strength of the welded joint; while when the Ti content is low, the titanium alloy layer contains more impurities or alloy elements, which are prone to adverse reactions with elements in the copper alloy or ceramics during welding to generate brittle intermetallic compounds, resulting in reduced joint strength.

[0011] Furthermore, the composition of the titanium alloy layer includes ≥95wt% Ti and the remainder includes impurities such as Fe, C, O and N. ≥95wt% Ti in the titanium alloy composition can also ensure a higher surface flatness when the titanium alloy is processed, so that the hydrogenation layer is evenly distributed.

[0012] Furthermore, the single layer thickness of the titanium hydride layer is 0.05-3 μm, such as 0.05 μm, 0.06 μm, 0.07 μm, 0.08 μm, 0.09 μm, 0.1 μm, 0.15 μm, 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm, 0.55 μm, 0.6μm, 0.65μm, 0.7μm, 0.75μm, 0.8μm, 0.85μm, 0.9μm, 0.95μm, 1.0μm, 1.1μm, 1.3μm, 1.5μm, 1.7μm, 1.9μm, 2.0μm, 2.2μm, 2.4μm, 2.6μm, 2.8μm, 3.0μm, etc. Although the titanium hydride layer can improve the wettability of the solder and protect the titanium alloy from oxidation, and promote the alloying process of welding, when the titanium hydride is too thick, it may cause the hydrogen content in the welded joint to be too high, forming a large amount of hydride, increasing the brittleness of the joint and reducing its plasticity and toughness; and hydrogen can easily enter the phase structure of the titanium alloy, and excessive hydrogen content will also cause more pores and defects in the welding area. Therefore, the thickness range of the titanium hydride single layer must be strictly controlled.

[0013] Furthermore, the titanium hydride is saturated titanium hydride or unsaturated titanium hydride, preferably unsaturated titanium hydride TiHx, wherein x is 1-2.

[0014] Secondly, the present invention also provides a method for preparing an active brazing material, comprising the following steps:

[0015] S1, soaking the pure titanium foil or titanium alloy foil in a first acid solution to remove the oxide film on the surface thereof;

[0016] S2, performing a hydrogenation treatment on the pure titanium foil or the titanium alloy foil to form a titanium hydride layer on the surface thereof;

[0017] S3, cleaning and drying the surface to obtain the active brazing material.

[0018] Furthermore, the present invention does not strictly limit the shape of the pure titanium foil or titanium alloy foil. In one embodiment, the pure titanium foil or titanium alloy foil is in the form of a sheet or a roll.

[0019] Furthermore, the thickness of the pure titanium foil or titanium alloy foil is 5-50μm, such as 5μm, 6μm, 7μm, 10μm, 15μm, 20μm, 22μm, 25μm, 28μm, 30μm, 32μm, 35μm, 38μm, 40μm, 43μm, 45μm, 47μm, 50μm, etc.; preferably 5-25μm, more preferably 7-15μm.

[0020] Furthermore, the content of Ti in the titanium alloy foil is ≥95wt%.

[0021] Furthermore, the first acid solution is at least one of a hydrofluoric acid solution, a mixed solution of nitric acid and hydrofluoric acid, a mixed solution of hydrochloric acid and hydrofluoric acid, sulfuric acid, and hydrochloric acid.

[0022] Preferably, the first acid solution is a hydrofluoric acid solution. The pickling process of S1 is to better remove pollutants and oxide films on the surface of pure titanium or titanium alloy, improve surface finish, and enhance solder quality; generally, the more sufficient the acid, the better, but titanium alloy has a strong affinity for hydrogen, and too long a treatment time or too high an acid concentration will lead to an increase in the hydrogen content in the titanium alloy, causing brittleness, deformation, and material rupture, which is not conducive to welding quality. The present invention uses a hydrofluoric acid solution and controls the acid concentration and treatment time to have a better oxide film removal effect and avoid excessive hydrogen absorption.

[0023] Furthermore, the volume concentration of the first acid solution is 1-15%, such as 1%, 2%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, etc.; preferably 2-10%, more preferably 3-7%. When the concentration is too high, the amount of hydrogen dissolved in the gap of the titanium alloy structure increases, which can also cause residual fluorine contamination and cause yellow spot defects on the surface of the titanium alloy.

[0024] Furthermore, the soaking time in step S1 is 5-100 s, more preferably 10-60 s.

[0025] Furthermore, the hydrogenation treatment in step S2 is performed by at least one of an acid soaking method, a hydrogen direct hydrogenation method, and an acid-hydrothermal method.

[0026] In one embodiment, the hydrogenation treatment in step S2 is carried out by acid soaking.

[0027] Furthermore, the components of the second acid solution used in the acid immersion method are concentrated hydrochloric acid and concentrated sulfuric acid, and the volume ratio of the concentrated hydrochloric acid to the concentrated sulfuric acid is 1.5-3:1. In the initial stage of hydrogenation, concentrated hydrochloric acid is highly corrosive to the surface of pure titanium or titanium alloy, and the amount of hydrogen absorbed by pure titanium or titanium alloy also increases significantly. When used in conjunction with concentrated sulfuric acid, the degree of corrosion can be increased slightly but the amount of hydrogen absorbed can be reduced. However, when the amount of concentrated sulfuric acid is too much, the unevenness of the scratches on the surface of the pure titanium or titanium alloy layer increases, and the scratches on some surfaces are deep and some are shallow. During welding, the interface contact and wetting between the solder surface and the substrate to be welded will deteriorate. Therefore, it is necessary to control the relative content of the two to ensure better hydrogenation efficiency, and to effectively control the hydrogen content of the hydrogenated titanium layer within a reasonable range, avoid the dissolution and diffusion of excessive hydrogen in the lattice pores of the titanium alloy, and improve the quality of solder brazing.

[0028] Furthermore, the soaking time in the acid soaking method is 15-90 min, preferably 20-80 min, and more preferably 30-60 min.

[0029] In one embodiment, the hydrogenation treatment in step S2 is carried out by an acid-hydrothermal method.

[0030] Furthermore, the acid used in the acid-hydrothermal method is a sulfuric acid solution; the concentration of the sulfuric acid solution is 0.2-14 mol / L, such as 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, 2mol / L, 3mol / L, 4mol / L, 5mol / L, 6mol / L, 7mol / L, 8mol / L, 9mol / L, 10mol / L, 11mol / L, 12mol / L, 13mol / L, 14mol / L, etc.; preferably 2-8 mol / L.

[0031] Furthermore, the reaction time of the acid-hydrothermal method is 5-20 hours, preferably 10-15 hours; the reaction temperature is 90-170° C., preferably 100-150° C. The effect of hydrogenation treatment of the titanium alloy surface using low-concentration sulfuric acid alone is not good, but the degree of hydrogenation will be improved under hydrothermal conditions, and the thickness and hydrogen content of the titanium hydride layer can be better controlled by controlling the hydrothermal reaction time and temperature and other condition parameters.

[0032] Furthermore, the single layer thickness of the titanium hydride layer in S2 is 0.05-3 μm.

[0033] Finally, the present invention also provides application of the active brazing material in a vacuum brazing process.

[0034] Furthermore, the active brazing material can be used in vacuum brazing of copper alloys and ceramics, copper alloys and nonferrous metals, copper alloys and carbon materials, etc.

[0035] Beneficial effects of the present invention:

[0036] (1) The present invention first removes the oxide film on the surface of pure titanium foil or titanium alloy foil, then performs hydrogenation treatment on the pure titanium foil or titanium alloy foil to generate dark gray titanium hydride on its surface, and finally washes and dries it to obtain an active brazing material. The titanium hydride layer on the surface of the active solder not only effectively prevents the oxidation of the brazing material and prolongs the service life of the brazing material, but also decomposes during the brazing process to produce titanium to improve the wetting effect, and the generated hydrogen plays a role in preventing oxidation, effectively improving the activation effect of the solder;

[0037] (2) Compared with active brazing materials such as electroplated solder sheets and solder paste, the active brazing material of the present application has simpler preparation steps, higher production efficiency, lower production cost and is more convenient for sample assembly;

[0038] (3) Processing pure titanium foil or titanium alloy foil of different sizes can produce large-area thin-layer welding sheets. While ensuring the uniformity of the solder, it can also effectively avoid defects such as voids and cracks at the brazing joints and improve the bonding strength of the welded joints;

[0039] (4) The present invention strictly controls the acid treatment process and the hydrogenation process in the preparation of the active brazing material. The two processes cooperate with each other to achieve a titanium hydride layer of appropriate thickness on the surface of the pure titanium layer or the titanium alloy layer, and can also control the hydrogen content in the titanium hydride layer and the hydrogen increment in the pure titanium layer or the titanium alloy layer, thereby ultimately improving the welding performance of the brazing material on the copper alloy and ceramic interface. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 : A flow chart of the preparation of the active brazing material in Example 1 of the present invention;

[0041] Figure 2 : A physical picture of the active brazing material prepared in Example 1 of the present invention;

[0042] Figure 3 : Metallographic image of the welded joint of the sample welded by the active brazing material of Example 1 of the present invention;

[0043] Figure 4 : A physical picture of the active brazing material prepared in Example 2 of the present invention;

[0044] Figure 5 : Metallographic image of the welded joint of the sample welded by the active brazing material of Example 2 of the present invention;

[0045] Figure 6 : A physical picture of the active brazing material prepared in Example 3 of the present invention;

[0046] Figure 7 : Metallographic image of the welded joint of the sample welded by the active brazing material of Example 3 of the present invention. DETAILED DESCRIPTION

[0047] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] Example

[0049] This embodiment provides a method for preparing an active brazing material, comprising the following steps:

[0050] S1. Soaking the pure titanium foil or titanium alloy foil in a first acid solution with a volume concentration of 1-15% for 5-100 seconds to remove the oxide film on the surface thereof;

[0051] The pure titanium foil or titanium alloy foil is in sheet or roll form with a thickness of 5-50 μm, the titanium alloy foil has a Ti content of ≥95wt%, and the composition includes ≥95wt% Ti and the remainder includes impurities such as Fe, C, O and N;

[0052] The first acid solution is at least one of a hydrofluoric acid solution, a mixed solution of nitric acid and hydrofluoric acid, a mixed solution of hydrochloric acid and hydrofluoric acid, sulfuric acid, and hydrochloric acid; preferably a hydrofluoric acid solution; the volume concentration of the first acid solution is preferably 2-10%, more preferably 3-7%; and the immersion time is preferably 10-60s.

[0053] S2, performing a hydrogenation treatment on the pure titanium foil or the titanium alloy foil to form a titanium hydride layer on the surface thereof;

[0054] Among them, the hydrogenation treatment is selected from the acid soaking method or the acid-hydrothermal method; the components of the second acid solution used in the acid soaking method are concentrated hydrochloric acid and concentrated sulfuric acid, the volume ratio of the concentrated hydrochloric acid and concentrated sulfuric acid is 1.5-3:1, and the soaking time is 15-90min, preferably 20-80min, and more preferably 30-60min.

[0055] The acid used in the acid-hydrothermal method is sulfuric acid solution; the concentration of the sulfuric acid solution is 0.2-14 mol / L; the reaction time is 5-20 hours, preferably 10-15 hours; the reaction temperature is 90-170°C, preferably 100-150°C.

[0056] S3, cleaning and drying the surface to obtain the active brazing material.

[0057] This embodiment also provides an active brazing material obtained according to the above preparation method, wherein the active brazing material is composed of a pure titanium layer or a titanium alloy layer and a titanium hydride layer distributed on both sides thereof; the thickness of the active brazing material is 3-48 μm, and the single layer thickness of the titanium hydride layer is 0.05-3 μm.

[0058] Example 1

[0059] This embodiment provides a method for preparing an active brazing material, comprising the following steps:

[0060] S1. Clean the surface of Ti alloy foil (specifications: 150 mm×190 mm×0.01 mm) with anhydrous ethanol, wipe it clean with dust-free paper and set aside; soak the Ti foil in a 5% volume concentration hydrofluoric acid solution for 15 s to remove the surface oxide film;

[0061] The composition of the Ti alloy foil includes ≥95wt% Ti, and the remainder includes impurities such as Fe, C, O and N, and the titanium alloy grade is TA3.

[0062] S2. Add 125 mL of concentrated sulfuric acid into 375 mL of concentrated hydrochloric acid and stir continuously. After the mixed solution of concentrated sulfuric acid and concentrated hydrochloric acid is cooled to room temperature, soak the Ti alloy foil in it for 40 min for hydrogenation treatment.

[0063] S3. After cleaning and drying, an active brazing material is obtained. The surface of the prepared active brazing material is dark gray and the thickness is 8-9 μm.

[0064] This embodiment also provides an active brazing material prepared according to the method, wherein the active brazing material is composed of a titanium alloy foil and a titanium hydride layer distributed on both sides thereof; wherein the thickness of the active brazing material is 8-9 μm; and the single layer thickness of the titanium hydride layer is 0.2-0.4 μm.

[0065] Attached Figure 3 This is a metallographic image of the welded joint of the sample welded with the active brazing material of this embodiment. It can be seen from the image that the active brazing material reacts with oxygen-free copper and silicon nitride ceramics during the brazing process to generate a continuous and uniform reaction layer. No welding defects such as voids and cracks are found at the welded joint, and a good bond can be achieved.

[0066] Example 2

[0067] A method for preparing an active brazing material is provided, comprising the following steps:

[0068] S1. Clean the surface of Ti alloy foil (specifications: 135 mm × 190 mm × 0.007 mm) with anhydrous ethanol, wipe it with dust-free paper and set aside; soak the Ti alloy foil in a hydrofluoric acid solution with a volume concentration of 8% for 10 s to remove the surface oxide film;

[0069] The composition of the Ti foil is consistent with that of Example 1.

[0070] S2. Add 100 mL of concentrated sulfuric acid into 300 mL of concentrated hydrochloric acid and stir continuously. After the mixed solution of concentrated sulfuric acid and concentrated hydrochloric acid is cooled to room temperature, soak the Ti foil in it for 30 min for hydrogenation treatment.

[0071] S3. After cleaning and drying, an active brazing material is obtained. The surface of the prepared active brazing material is dark gray and the thickness is 6-7 μm.

[0072] This embodiment also provides an active brazing material prepared according to the method, wherein the active brazing material is composed of a titanium alloy foil and a titanium hydride layer distributed on both sides thereof; wherein the thickness of the active brazing material is 6-7 μm; and the single layer thickness of the titanium hydride layer is 0.1-0.3 μm.

[0073] Attached Figure 5 This is a metallographic diagram of the welded joint of the sample welded by the active brazing material of this embodiment. It can be seen from the figure that the oxygen-free copper and the ceramic are well bonded, and the reaction at the interface generates a uniformly distributed reaction layer. This solution can also achieve a reliable connection between oxygen-free copper and silicon nitride ceramics.

[0074] Example 3

[0075] A method for preparing an active brazing material is provided, comprising the following steps:

[0076] S1. Clean the surface of Ti alloy foil (specifications: 150 mm × 190 mm × 0.01 mm) with anhydrous ethanol, wipe it with dust-free paper and set aside; soak the Ti alloy foil in a 2% volume concentration hydrofluoric acid solution for 50 seconds to remove the surface oxide film;

[0077] The composition of the Ti foil is consistent with that of Example 1.

[0078] S2. Take 54 mL of concentrated sulfuric acid and dilute it to 100 mL with water to obtain a sulfuric acid solution with a concentration of 10 mol / L. Pour the sulfuric acid solution into an autoclave and put the Ti alloy foil into it. Heat the autoclave to 130°C and keep it warm for 12 h for hydrogenation treatment.

[0079] S3. After cleaning and drying, an active brazing material is obtained. The surface of the prepared active brazing material is dark gray and the thickness is 9-10 μm.

[0080] This embodiment also provides an active brazing material prepared according to the method, wherein the active brazing material is composed of a titanium alloy foil and a titanium hydride layer distributed on both sides thereof; wherein the thickness of the active brazing material is 7-8 μm; and the single layer thickness of the titanium hydride layer is 0.3-0.5 μm.

[0081] Attached Figure 7 This is a metallographic image of a welded joint of a sample welded with the active brazing material of this embodiment. As can be seen from the image, oxygen-free copper and ceramic are well bonded and a reliable connection between the two can be formed.

[0082] Example 4

[0083] A method for preparing an active brazing material is provided, comprising the following steps:

[0084] S1. Clean the surface of pure Ti foil (specifications: 135 mm × 190 mm × 0.05 mm) with anhydrous ethanol, wipe it with dust-free paper and set aside; soak the pure Ti foil in a 10% volume concentration hydrofluoric acid solution for 10 s to remove the surface oxide film.

[0085] S2. Add 80 mL of concentrated sulfuric acid into 320 mL of concentrated hydrochloric acid and stir continuously. After the mixed solution of concentrated sulfuric acid and concentrated hydrochloric acid is cooled to room temperature, the pure Ti foil is immersed in it for 60 min for hydrogenation treatment.

[0086] S3. After cleaning and drying, an active brazing material is obtained. The surface of the prepared active brazing material is dark gray and the thickness is 8-9 μm.

[0087] This embodiment also provides an active brazing material prepared according to the method, wherein the active brazing material is composed of pure titanium foil and titanium hydride layers distributed on both sides of the foil; wherein the thickness of the active brazing material is 8-9 μm; and the single layer thickness of the titanium hydride layer is 0.6-0.8 μm.

[0088] Example 5

[0089] A method for preparing an active brazing material is provided, comprising the following steps:

[0090] S1. Clean the surface of Ti alloy foil (specifications: 150 mm × 190 mm × 0.01 mm) with anhydrous ethanol, wipe it with dust-free paper and set aside; soak the Ti alloy foil in a 5% volume concentration hydrofluoric acid solution for 30 seconds to remove the surface oxide film;

[0091] The composition of the Ti alloy foil is consistent with that of Example 1.

[0092] S2. Take 155.6 mL of concentrated sulfuric acid and dilute it to 200 mL with water to obtain a sulfuric acid solution with a concentration of 14 mol / L. Pour the sulfuric acid solution into an autoclave and put the Ti alloy foil into it. Heat the autoclave to 100°C and keep it warm for 10 h to carry out hydrogenation treatment.

[0093] S3. After cleaning and drying, an active brazing material is obtained. The surface of the prepared active brazing material is dark gray and the thickness is 9-10 μm.

[0094] This embodiment also provides an active brazing material prepared according to the method, wherein the active brazing material is composed of a titanium alloy foil and a titanium hydride layer distributed on both sides thereof; wherein the thickness of the active brazing material is 9-10 μm; and the single layer thickness of the titanium hydride layer is 0.2-0.4 μm.

[0095] Comparative Example 1

[0096] This comparative example provides a method for preparing an active brazing material; it is basically the same as that of Example 1, except that: the specification of the Ti alloy foil is 150 mm×190 mm×0.07 mm.

[0097] Comparative Example 2

[0098] This comparative example provides a method for preparing an active brazing material; it is basically the same as Example 1, except that the composition of the titanium alloy foil is 92% Ti and the remainder is impurities.

[0099] Comparative Example 3

[0100] This comparative example provides a method for preparing an active brazing material; it is basically the same as Example 1, except that the Ti alloy foil is immersed in a hydrofluoric acid solution with a volume concentration of 15% for 15 seconds to remove the surface oxide film.

[0101] Comparative Example 4

[0102] This comparative example provides a method for preparing an active brazing material; it is basically the same as Example 1, except that: in S2, 200 mL of concentrated sulfuric acid is added to 200 mL of concentrated hydrochloric acid and stirred continuously, and after the concentrated sulfuric acid and concentrated hydrochloric acid mixed solution is cooled to room temperature, the Ti alloy foil is immersed in it for 40 minutes for hydrogenation treatment.

[0103] Comparative Example 5

[0104] This comparative example provides a method for preparing an active brazing material; it is basically the same as Example 1, except that: 125 mL of concentrated sulfuric acid is added to 375 mL of concentrated hydrochloric acid and stirred continuously, and after the concentrated sulfuric acid and concentrated hydrochloric acid mixed solution is cooled to room temperature, the Ti alloy foil is immersed in it for 90 minutes for hydrogenation treatment.

[0105] Comparative Example 6

[0106] This comparative example provides a method for preparing an active brazing material; it is basically the same as Example 1, except that: 125 mL of concentrated sulfuric acid is added to 375 mL of hydrofluoric acid (volume fraction is 10%) and stirred continuously, and after the acid mixed solution is cooled to room temperature, the Ti alloy foil is immersed in it for 40 minutes for hydrogenation treatment.

[0107] Comparative Example 7

[0108] This comparative example provides a method for preparing an active brazing material; it is basically the same as Example 3, except that: the reactor is heated to 160° C. and kept warm for 12 h, and hydrogenation treatment is performed.

[0109] Performance testing methods and results:

[0110] The active brazing material prepared in the above embodiment is used to braze oxygen-free copper and silicon nitride ceramic sheets of the same specifications. The welding rate of the joint is characterized by an ultrasonic acoustic microscope. The scanning range takes the entire welding joint area, and the data is obtained and the porosity is calculated using Image-J software. The peel strength of the welding sample is then tested according to GB / T 4722-2017 standard. The results are shown in Table 1.

[0111] Table 1

[0112]

[0113] Analysis: It can be seen from the above table that the brazing materials of Examples 1-5 of the present application have excellent brazing properties. During the brazing process, they react with oxygen-free copper and silicon nitride ceramics to generate a continuous and uniform reaction layer. No welding defects such as voids and cracks are found at the welded joints, and good bonding can be achieved. After testing, the peel strength and porosity at the joints are relatively excellent.

[0114] In Comparative Example 1, a thicker titanium alloy foil is used, which may make it difficult for the brazing material to be completely melted, resulting in a small amount of cold welding defects in the joint, reducing the mechanical properties of the joint and increasing the porosity.

[0115] Compared with Example 1, Comparative Example 2 uses an alloy foil with a Ti content of 92%, which has a lower titanium content. After the titanium alloy is surface treated, the surface flatness decreases, causing uneven distribution of hydrogenation layer products, which ultimately affects the brazing performance of the brazing material.

[0116] Comparative Examples 3-6 demonstrate that adjusting the acid concentration, acid type, treatment time and other process parameters of the titanium alloy foil surface treatment and hydrogenation treatment will affect the welding performance of the brazing material. Only when the above parameters are within the specified appropriate range can an ideal brazing effect be obtained.

[0117] In Comparative Example 7, the temperature of the acid-hydrothermal method is increased, which will produce a thicker titanium hydride layer and allow more hydrogen to enter the phase structure of the titanium alloy, resulting in more pores and defects in the welding area, ultimately having a significant adverse effect on the joint.

[0118] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0119] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. An active brazing material, characterized in that: The active brazing material is composed of a titanium alloy layer or a pure titanium layer and a titanium hydride layer distributed on both sides thereof; the thickness of the titanium alloy layer or the pure titanium layer is 5-50 μm; the single layer thickness of the titanium hydride layer is 0.05-3 μm; the preparation method of the active brazing material comprises the following steps: S1, soaking the pure titanium foil or titanium alloy foil in a first acid solution to remove the oxide film on the surface thereof; S2, performing a hydrogenation treatment on the pure titanium foil or the titanium alloy foil to form a titanium hydride layer on the surface thereof; S3, cleaning and drying the surface to obtain the active brazing material; The first acid solution is a hydrofluoric acid solution, and the volume concentration of the first acid solution is 1-15%; the immersion time of step S1 is 5-100s; The hydrogenation treatment in step S2 is carried out by acid soaking; the components of the second acid solution used in the acid soaking method are concentrated hydrochloric acid and concentrated sulfuric acid, and the volume ratio of the concentrated hydrochloric acid to the concentrated sulfuric acid is 1.5-3:1; the soaking time is 15-90 min.

2. The active brazing material according to claim 1, characterized in that: The content of Ti in the titanium alloy layer is ≥95wt%.

3. The active brazing material according to claim 1, characterized in that: The titanium hydride is saturated titanium hydride or unsaturated titanium hydride.

4. The active brazing material according to claim 1, characterized in that: The hydrogenation treatment in step S2 is carried out by an acid-hydrothermal method; the acid used in the acid-hydrothermal method is a sulfuric acid solution, the concentration of the sulfuric acid solution is 0.2-14 mol / L, the reaction time of the acid-hydrothermal method is 5-20 h, and the reaction temperature is 90-170°C.

5. The use of the active brazing material according to any one of claims 1 to 4 in a vacuum brazing process, characterized in that: The active brazing material is used for vacuum brazing of any one of copper alloy and ceramic, copper alloy and nonferrous metal, and copper alloy and carbon material.

Citation Information

Patent Citations

  • Brazing material, method for producing same, and method for producing metal-ceramic bonded substrate

    CN115151371A

  • Silver-copper-titanium brazing filler metal and preparation method and application thereof

    CN116038179A

  • improvements to the ceramic sealing process

    FR1155921A

  • Titanium hydride coated brazing product

    US5186380A